Gastric hyperplastic polyps: immunohistochemical characteristic of proliferation and apoptosis - V. A. Tumanskiy; T. A. Khrystenko (Patologìâ)
Aim. In order to research proliferation and apoptosis immunohistochemical study of expression of Ki-67 and Caspase-3 inbiopsies of 42 gastric hyperplastic polyps was conducted.